Pathophysiology and Theranostic Approaches to CanineCognitive Dysfunction Syndrome - Khare, Apeksha; Verma, Yash Kumar; Dubey, Amita; Verma, Yamini; Swamy, Madhu; Khare, Ankur (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Canine cognitive dysfunction syndrome is a common behavioral disorder of geriatric dogs prevailing in the world including India. The etiology is not confirmed yet, however, the main pathological change is age-related and progressive amyloid protein deposition in the brains of affected dogs. The syndrome usually goes unnoticed due to unawareness among caretakers and non-specific clinical signs such as altered behaviour and cognition. When detected early, environmental enrichment, nutritive diet and supportive therapeutic agents can be beneficial in procrastinating the disorder and improving the quality of life of the animal.